Impact of IFRS on the accounting numbers of Romanian listed companies - Costel Istrate (Journal of Accounting and Management Information Systems (JAMIS), 2014)
The accession of Romania to EU – in 2007 - confirmed the mandatory application IFRS in the consolidated financial statements of Romanian listed companies. From 2012, the application of IFRS is extended to the separate financial statements of the listed companies. Applying the Gray index of comparability, we attempt to measure the impact of the transition to IFRS on the accounting figures for the comparative year 2011. Our findings (slight increase of equities, decrease in income, ROA, ROE, ROS, increase in leverage) suggests that the impact of IFRS on Romanian companies is not very important and is not always in the same direction as the changes that occurs in countries that belong to the European continental accounting model.
Keywords: M41; 650; IFRS impact; Romania; index of comparability; European accounting system; neutrality